Analisis Teks Dalam Terjemahan Tidak Langsung: Kajian Kes Nurani Tanah Melayu - Zainol, Intan Suraya (2021)
The translation process typically involves two main elements, namely a source text and a translated text. Although translations are usually carried out directly from the original source text, there are also translations that result from an intermediate text, i.e. a text that is also a translation from the original source text. A translated text derived from an intermediate text is referred to as an indirect translation. The main issues with indirect translation are assumptions about the influence of the intermediate text and concerns over fidelity to the original source text. In unraveling the truth about this assumption, this study examines the changes that take place between the translated text, the intermediate text and the original source text. These changes are then studied in more detail by looking into the adjustments made by the translator. Finally, the study also took into account the response of the translator regarding the process of indirect translation and the justification for the changes made to the translated text. To examine this issue, the study focuses on an indirect translation in Malay entitled Nurani Tanah Melayu, the English intermediary text entitled The Soul of Malaya, and the original French source text entitled Malaisie. To carry out this study, the source text in French is compared to its English and Malay translations. The lexical analysis points to to the fact that there are differences between the translated text, the intermediate text and the original source text. Changes between these texts are elaborated by discussing the changes made in terms of additions, omissions and amendments.